Using Test Standard-Setting Methods in Educational Program Evaluation: Addressing the Issue of How Good is Good Enough - Paul R. Brandon (The Evaluation Center at Western Michigan University, 2005)
School districts in the United States and elsewhere commonly use standard setting to assign value to student test and assessment scores. That is, they set standards to show "how good is good enough." This paper presents a summary of the empirical findings on the most widely-studied test standard-setting method and describes what the conclusions of the summary suggest about the use of test standard-setting in educational program evaluations.